Reaganland : America's right turn, 1976-1980 - Perlstein, Rick, 1969- (Simon & Schuster, 2020)
Connects the activities and influence of today's conservative movements to a deliberate shift toward right-wing policies that began during the Carter administration and led to the election of Ronald Reagan in 1980.